Implementing Java Distributed Objects (International Journal of Engineering and Computer Science, 2015)
— Organizations rely on information to make effective business decisions and corporate intranets are changing the way organizations conduct business. As networking technologies continue to improve, with increasing bandwidth and reliability, effective distributed computing is becoming a reality. Organizations are relying on internet technologies to be the conduit for employees to access and manipulate corporate information. Having timely and accurate information is essential for effective management practices and optimization of limited resources. Information can be stored effectively and efficiently in Server object & Client object can access it through distributed computing. Two popular methods for distributed computing are RMI and CORBA. RMI uses rmi protocol and CORBA uses IIOP protocol